Decay of Enterococcus faecalis, Vibrio cholerae and MS2 Coliphage in a Laboratory Mesocosm Under Brackish Beach Conditions - Tiwari, Ananda; Kauppinen, Ari; Pitkänen, Tarja (Frontiers in Public Health, 2019)
Enterococci are fecal indicator bacteria (FIB) used for monitoring the microbial quality of bathing water. However, the reliability of health protection by monitoring FIB is questioned. This study evaluated the decay pattern of Enterococcus faecalis in beach environment and compared it with decay patterns of the pathogen Vibrio cholerae and the virus indicator MS2 coliphage. Tests were done in an experimental mesocosm simulating natural Nordic summer daylight conditions with and without the aquatic plant Myriophyllum sibiricum. The decay of the spiked test microbes (E. faecalis, V. cholerae and MS2) was enumerated up to 27 days from two coastal bathing water mesocosms with subtidal sediment. E. faecalis and V. cholerae exhibited non-linear biphasic decay patterns and were detected upmost towards the end of the experiment in the water, sediment, and vegetation. The gene copies of V. cholerae dropped to a minimum by days 6–8 but then the numbers increased back up to nearly the spiked level. The MS2 coliphage was detected only up to 8-10 days into the experiment solely in the water where a log-linear decay pattern was seen. The test microbe, sample origin (water, sediment or vegetation) and for E. faecalis the enumeration method (culture-based or qPCR) affected the decay pattern. E. faecalis decayed faster in water than in sediment and vegetation. Positive correlations between culturable E. faecalis counts with V. cholerae gene copies and MS2 counts were recorded on the first few days of the experiment. This study demonstrated the important role of water, sediment and vegetation regarding the partitioning of pathogens and fecal indicators in coastal environment. The enumeration of the enterococci counts alone was not sufficient for predicting the numbers of pathogens such as Vibrio spp. in bathing water. The growth of Vibrio spp. in the Baltic Sea deserves more attention and might require water quality monitoring to be applied for these pathogens in the coming years due to the predicted rise in sea surface temperature favoring Vibrio spp. growth. Further, different decay patterns observed between MS2 and enterococci emphasize the need for and importance of a viral indicator in assessing water quality more comprehensively.